A Cross-Sectional Study of the Relationship Between Mental Health Problems and Overweight and Obesity in Adolescents - Bjertnaes, Asborg Aanstad; Fossum, Ingrid Nesdal; Oma, Ingvild; Bakken, Kjersti Sletten; Arne, Tor; Holten-Andersen, Mads Nikolaj (Frontiers in Public Health, 2020)
Background: There is a suggested coexistence between obesity and mental health discomfort in adolescence. The objective of this study was to explore if mental health indices covaried with body mass index (BMI) in adolescence and if there were gender-related disparities. Methods: Data were collected in two cross-sectional surveys of 10th-grade students (15 to 16 years old) carried out in 2002 and 2017. The questionnaires included self-reported height and weight, questions covering mental health using the Strengths and Difficulties Questionnaire (SDQ), lifestyle, and sociodemographic variables. We estimated the associations between SDQ subscale scores and BMI and the prevalence of overweight and obesity in linear and logistic multivariable models. We also estimated the extent to which gender modified these associations. Results: BMI was positively associated with peer problems [beta (β): 0.08, (95% confidence interval 0.01, 0.14)], indicating that for every point increase in peer problems subscore, BMI increased by 0.08 kg/m2. The association between internalizing (i.e., peer and emotional) problems and BMI and conduct problems and BMI was different for boys and girls (p < 0.05 for all effect modifications). Conclusion: In this repeated cross-sectional study across 15 years, we found that peer problems were associated with BMI in Norwegian adolescents. We also found that there is a possibility that adolescent boys and girls report different mental health symptoms related to increased BMI. This finding implicates a need for gender-specific attention when assessing risk factors for increased BMI in adolescents.